Human resource practices and innovation activity in Malaysian SMEs - Hashim, Mohd Khairuddin; Mahajar, Abdul Jumaat; Ahmad, Sa'ari (Universiti Utara Malaysia Press, 2005)
Although the literature suggests human resource practices stimulate innovation in organizations, limited studies have investigated the relationships between human resource practices and innovation activity in organizations, particularly in the small and medium-sized enterprises (SMEs). This study attempts to address this issue by examining the relationships between human resource practices and innovation activity of 48 small and medium-sized enterprises in the Malaysian manufacturing sector. The findings of the empirical research indicate significant positive relationships between human resource practices and the innovation activity of the SMEs.